Low Expression of FFAR2 in Peripheral White Blood Cells May Be a Genetic Marker for Early Diagnosis of Acute Myocardial Infarction - Jianjun Ruan; Heyu Meng; Xue Wang; Weiwei Chen; Xiaomin Tian; Fanbo Meng (Cardiology Research and Practice)
Objective. To find molecular markers for the diagnosis of acute myocardial infarction (AMI), this research further verified the relationship between the expression level of FFAR2 gene and AMI by expanding the sample size based on the previous gene chip results. Methods. Peripheral venous leukocytes were collected from 113 patients with AMI and 94 patients with noncoronary artery disease as the experimental group and the control group, respectively. Real-time fluorescence quantitative polymerase chain reaction was used to detect the expression of the FFAR2 gene. Western blot analysis was applied to detect the relative expression of the FFAR2 gene at the level of protein. Furthermore, the relationship between gene expression and clinical data was also analyzed and compared. Results. The level of expression of FFAR2 gene in peripheral blood of patients with AMI was significantly lower than that of the control group (0.33 [0.04–1.08], 0.62 [0.07–1.86], respectively; p<0.05), which was 0.53 times that of the control group. Western blot results presented that the FFAR2 protein level in the peripheral blood of the AMI group was lower than that of the control group (0.114; p=0.004). Analyzing clinical data of the subjects indicated that the average age of the AMI group was significantly higher than the age of control group (p<0.01). Also, the fasting blood glucose level was higher (p<0.01), and the high-density lipoprotein cholesterol (HDL-C) level was lower (p=0.03). The FFAR2 mRNA level correlated positively with the HDL-C level (p<0.01). Logistic regression analysis suggested that the low expression of the FFAR2 gene in peripheral blood may be a risk factor for AMI independent of age, family history of diabetes, fasting blood glucose level, and HDL-C level (p=0.025). Compared with the high FFAR2 expression group, the risk of AMI in the low FFAR2 expression group was 6.308 times higher. Conclusion. The expression level of the FFAR2 gene in peripheral blood of patients with AMI was significantly lower than that in the control group. Low expression of the FFAR2 gene in peripheral blood is an independent risk factor for AMI. Hence, it may also be a potential biomarker to predict AMI.